2022
DOI: 10.3390/polym14020220
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvents for Starch Treatment

Abstract: In this review, the application of deep eutectic solvents (DESs) as starch solvents, plasticizers and for other treatment has been described. Starch, as one of the most abundant biopolymers, is considered for forming new biodegradable materials. This new approach, referring to applying deep eutectic solvents for dissolving starch, its plasticization and other modifications, was presented. A DES could be a good alternative for common starch plasticizers (e.g., glycerol, urea) as well as recently considered ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…ILs and DESs are considered to be excellent solvents of polysaccharides, and also alternative plasticizers of polysaccharide‐based packaging (Khajavian et al., 2022; Skowrońska & Wilpiszewska, 2022; Zhou et al., 2022). Comparing with traditional solvents, many properties (i.e., solubility, toxicity, and biological activity) of ILs and DESs can be calibrated by changing anions and cations, or hydrogen bond donor/acceptor, according to their applications to improve their performance as task‐specific solvents.…”
Section: Ils and Dess And Their Properties For Polysaccharide‐based P...mentioning
confidence: 99%
See 3 more Smart Citations
“…ILs and DESs are considered to be excellent solvents of polysaccharides, and also alternative plasticizers of polysaccharide‐based packaging (Khajavian et al., 2022; Skowrońska & Wilpiszewska, 2022; Zhou et al., 2022). Comparing with traditional solvents, many properties (i.e., solubility, toxicity, and biological activity) of ILs and DESs can be calibrated by changing anions and cations, or hydrogen bond donor/acceptor, according to their applications to improve their performance as task‐specific solvents.…”
Section: Ils and Dess And Their Properties For Polysaccharide‐based P...mentioning
confidence: 99%
“…On the contrary, elongation at break increased with the amount of the DESs, and the highest values are about 200% with 80% addition of ChCl/malonic DES (Jakubowska et al., 2020). Applications of DESs in polysaccharides (i.e., starch, chitin/chitosan), especially focusing on their structure and chemical properties, have been outlined (Khajavian et al., 2022; Özel & Elibol, 2021; Skowrońska & Wilpiszewska, 2022). However, regarding polysaccharide‐based films, only limited studies on the production of films with DESs as plasticizers were recently reported.…”
Section: Dess As Components Used In Polysaccharide‐based Packagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its lower cost and great environment-friendliness, deep eutectic solvents are regarded as alternatives to ionic liquids and are widely applied in various fields, including bio-analysis, pharmaceutical synthesis, and gas collection. [30][31][32] The development of natural deep eutectic solvents further highlights the advantages. 33,34 In such a case, both the hydrogen bond donor and hydrogen bond acceptor of the natural deep eutectic solvent are natural materials, such as quaternary ammonium salts, acids and amino acids.…”
Section: Introductionmentioning
confidence: 99%